A STUDY ON THE EFFECT OF SILICA FUME ON THE PROPERTIES OF RECYCLED AGGREGATE CONCRETE - Raj, I.R. Isan; Shanmugavalli, B. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Making use of demolished waste of reinforced concrete structures is one of the possibilities of reducing waste management and saving natural aggregates. This study presents an experimental investigation on the effect of silica fume (SF) on various strength properties of recycled coarse aggregate (RCA) concrete. In the present investigation, recycled coarse aggregate was used as 10%, 20%, 30%, 40% and 50% replacement of natural coarse aggregate in addition to silica fume partially replaces 10% of cement by weight. Properties such as Density, Water absorption, Compressive strength and Split tensile strength for M40 grade of concrete was prepared using recycled coarse aggregate and silica fume were studied and the results are compared with the natural coarse aggregate concrete.